Ground surface temperature variability and permafrost distribution over mountainous terrain in northern Mongolia. Issue 1 (1st January 2020) - Munkhjargal, Munkhdavaa; Yadamsuren, Gansukh; Yamkhin, Jambaljav; Menzel, Lucas
ABSTRACT: Permafrost plays an important role in numerous environmental processes at high latitudes and in high mountain areas. The identification of mountain permafrost, particularly in the discontinuous permafrost regions, is challenging due to limited data availability and the high spatial variability of controlling factors. This study focuses on mountain permafrost in a data-scarce environment of northern Mongolia, at the interface between the boreal forest and the dry steppe mid-latitudes. In this region, the ground temperature has been increasing continuously since 2011 and has a high spatial variability due to the distribution of incoming solar radiation, as well as seasonal snow and vegetation cover. We analyzed the effect of these controlling factors to understand the climate–permafrost relationship based on in situ observations. Furthermore, mean ground surface temperature (MGST) was calculated at 30-m resolution to predict permafrost distribution. The calculated MGST, with a root mean square error of ±1.4°C, shows permafrost occurrence on north-facing slopes and at higher elevations and absence on south-facing slopes. Borehole temperature data indicate a serious wildfire-induced permafrost degradation in the region; therefore, special attention should be paid to further investigations on ecosystem resilience and climate change mitigation in this region.